2007
DOI: 10.3343/kjlm.2007.27.5.313
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Acute Myeloid Leukemia without HLA-DR Expression

Abstract: Immunophenotype is one of the most useful tool for the identification of leukemia subtypes [1][2][3][4][5] and can be assigned within a few hours after bone marrow sampling.The typical immunophenotypic feature of acute promyelocytic leukemia (APL) has been reported as CD34-, HLA-DR-, CD13+, and CD33+ [6][7][8]. It has been reported that HLA-DR antigens are consistently negative in APL, whereas the majority of non-APL cases are positive for HLA-DR expression [9,10]; therefore, HLA-DR negativity is known to be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 14 publications
2
23
0
2
Order By: Relevance
“…These HLA-DR neg non-APL cases (further referred to as DR À AML in contrast to APL and DR þ AML) often resemble cytomorphologic features of hypogranular APL and belong almost exclusively to the myeloid AML subtypes (7,9,16). Published studies comparing APL and DR À AML cases with respect to CD34 expression and lineage infidelity, i.e., detecting the expression of CD2, CD56, CD19, or CD7, reported discrepant results (7,9,(15)(16)(17).…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…These HLA-DR neg non-APL cases (further referred to as DR À AML in contrast to APL and DR þ AML) often resemble cytomorphologic features of hypogranular APL and belong almost exclusively to the myeloid AML subtypes (7,9,16). Published studies comparing APL and DR À AML cases with respect to CD34 expression and lineage infidelity, i.e., detecting the expression of CD2, CD56, CD19, or CD7, reported discrepant results (7,9,(15)(16)(17).…”
mentioning
confidence: 90%
“…Published studies comparing APL and DR À AML cases with respect to CD34 expression and lineage infidelity, i.e., detecting the expression of CD2, CD56, CD19, or CD7, reported discrepant results (7,9,(15)(16)(17). Besides the rather small cohorts investigated, these studies also showed profound methodological differences, e.g., in blast gating strategies and in the threshold values used for HLA-DR and/or other antigen expression ranging from 10 to 20% (7,9,(15)(16)(17). Little detailed information about correlations with cytogenetic and novel molecular features are available.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5 A variety of previously published data reports on non-APL AML with lack of HLA-DR expression. [6][7][8] Most cases were AML M1/M2 and a high frequency of FLT3-ITD was observed. However, neither a complete and characteristic immuno- Letters to the Editor phenotype nor a clear-cut genetic background has been observed in these studies.…”
Section: Mll-ptdmentioning
confidence: 99%